La ilegalidad no formulada: Vivencias de estudiantes de derecho en su contacto con el mundo profesional - (:unkn) unknown (Pontificia Universidad Católica del Perú, 2024)
In their first contact with the professional world, law students experience diverse situations in which the law that regulates their internships is violated. In this research, we seek to understand how law students formulate those experiences, that is, t...
Keywords: Estudiantes de derecho; Ilegalidad